Misi: Dari Pembebasan ke Perutusan - Sriwahyuni, Teresa Lina (Lux et Sal, 2025)
Jubilee year and mission have a closely interwind relationship. The very core of mission is God’s salvific plan which is His desires to restore humanity in His likeness. To accomplish this mission, God sent prophets to proclaim His word; the Israelites to bring blessings to all nations, and ultimately, His only son to redeem the world. God has used many ways to save humanity. One of these is noted in Spes non Confundit, the Bull of Indiction by Pope Francis, No. 10 “This is an ancient appeal, one drawn from the word of God, whose wisdom remains ever timely. It calls for acts of clemency and liberation that enable new beginnings: “You shall hallow the fiftieth year, and you shall proclaim liberty throughout the land to all its inhabitants” (Lev 25:10) This Mosaic law, was later echoed by the Prophet of Isaiah, “The Lord has sent me to bring good news to the oppressed, to bind up the broken-hearted, to proclaim liberty to the captives and release to the prisoners, to proclaim the year of the Lord’s favour” (Is 61:1-2). This passage from Isaiah was then proclaimed by Jesus at the beginning of His ministry. From this exploration, one can say that mission is the restoration of humanity to God’s likeness through the proclamation of freedom for captives, recovery of sight for the blind, and liberation for the oppressed-just as in the jubilee year.